Efeito antirreabsortivo do alendronato e da combinação entre alendronato e atorvastatina na periodontite induzida por ligadura em ratos - Dutra, Paula Góes Pinheiro (2012)
Periodontal disease is an infectious-inflammatory disease, and drugs have been studied as modulators of this inflammatory process. In this context, this thesis, constituted by 3 articles had by objective: (1) Perform a review about the effect of Bisphosphonates (BPs) on periodontal disease; (2) Investigate the effect of Alendronate (ALD) on Bone-specfic Alkaline Phosphatase (BALP) on alveolar bone loss (ABL) in rats; (3) Evaluate the effect of ALD and Atorvastatin (ATV) combination on ABL in rats. On study 1, we sought in data basis, using the keywords “Bisphosphonates” and “Periodontitis”, pre-clinical and clinical studies, published in English and Portuguese, in the last 10 years. On study 2, 36 Wistar male rats, submitted to ligature-induced periodontitis, received 0.9% Saline (SAL) or ALD on the doses of 0.01; 0.05; 0.25 mg/kg-s.c., 30 min before ligature placement and daily during 11 days. It was evaluated: ABL (morphometry and histology) serum levels of Bone-specific Alkaline Phosphatase (BALP), transaminases, and Total Alkaline Phosphatase (TAP); and leukogram and corporal mass. On study 3, 78 Wistar male rats, submitted to ligature-induced periodontitis, received prophylactically (P): SAL or ALD (0.01; 0.25 mg/kg-s.c) or ATV (0.3; 27 mg/kg-v.o.) or the combination ALD+ATV (0.25+27; 0.01+0.3; 0.25+0.3; 0.01+27 mg/kg), 30 min before ligature and daily for 11 days; or the combination ALD+ATV (0.01+0.3 mg/kg) administered therapeutically (T), from the 5th day after ligature until the sacrifice. It was evaluated: ABL [morphometry, histology, histometry; immunohistochemistry for tartrate resistant acid phosphatase (TRAP); myeloperoxidase (MPO); BALP, transaminases; Leukogram and corporal mass]. The study 1 showed that BPs presented anti-resorptive and anti-inflammatory effects, reduced FAO and Telopeptide N-terminal of type I collagen (NTx) and improved periodontal clinical parameters. On article 2, ALD (0.25 mg/kg) prevented BALP and ABL reduction, and did not alter transaminases serum levels, but reduced TAP serum levels (p<0.05), it reduced neutrophilia and lymphomonocytosis (p<0.05), without causing important loss of weight. On the 3rd study, the isolated treatments in high doses, and all combinations controlled ABL (p<0.05). Low doses combination of ALD+ATV controlled ABL (P [38.96%] or T [53.53%]). The histological, histometric (p<0.05) and immunohistochemical analysis corroborated macroscopical findings. The low dose combination of ALD+ATV reduced MPO activity, prevented BALP reduction, reduced neutrophilia and lymphomonocytosis (p<0.05), without altering transaminases serum levels and without causing loss of weight. In this way, we can conclude that BPs presented anti-resorptive and anti-inflammatory effects reduced levels of biochemical markers of bone metabolism and improved periodontal parameters. ALD, administered isolated prevented BALP and ABL reduction, without causing systemic problems, and the combination of ALD+ATV, in low doses, reduced ABL and periodontal inflammation, without causing important systemic alterations as well.